Evaluation of the Applied Set of Exercises with the Intended Purpose to Improve the Abdominal Muscle Strength of the Cheerleader Students at UNWE - Ignatova, Milena; Dikova, Petya (Research Papers, 2021)
In the present study, we evaluate the effect of applied set of exercises over the abdominal muscles of the Cheerleading team at UNWE.To confirm our theory that significant impact on the abdominal muscles' strength during cheerleading trainings will improve it, we conducted a one-year study during 2018/2019 academic year. Twenty-six female students from UNWE took part in it, divided in two separate groups. The first group consisted of thirteen female students, currently playing in the cheerleading team. The second control group was formed by thirteen former cheerleader competitors. The groups executed the exercises provided in the approved curriculum.The results of the applied set of exercises were subjected to mathematical and statistical processing, thus proving the successfulness of the experiment. Furthermore, it is necessary to continue observing new possibilities for greater intensity and efficiency in the implementation of the training program. This will lead to better sport results.
Keywords: Cheerleading; Abdominal muscles; Female students